Protective Effect of Silk Lutein Extract on Hydrogen Peroxide Induced Retinal Pigment Epithelial Cells Damage - Aonsri, Chomphunut; Sutheerawattananonda, Manote; Limpeanchob, Nanteetip (Journal of Basic and Applied Pharmacology, 2015)
Oxidative stress in retinal pigment epithelial (RPE)cells plays a key role in age-related macular degeneration (AMD). There is clinical and cellular evidence that lutein as a dietary supplement can delay the disease due to its antioxidant actions which protects RPE cells. However, there is little data on the efficacy of luteins from different sources, so in this study, the protectant actions of lutein extracted from yellow silk cocoons was compared with two commercial luteins isolated from marigold flowers assessed by H2O2-induced oxidative damage in ARPE-19 cells. After 400µM H2O2 treatment, cell viability was reduced approximately 60% and intracellular ROS and lipid peroxidation were increased mostly 2 and 3 folds, respectively. The decreased activities of three major antioxidant enzymes including superoxide dismutase, glutathione peroxidase, and catalase were also observed. With different potency, all three tested luteins (at 1, 10 and 50 µM) could dose-dependently diminish such effects of H2O2. Silk lutein extract showed the most effective cell protection and anti-cellular oxidative stress by most measurements. Two marigold luteins also differently displayed their cell protection and antioxidant capacity. These data indicated that lutein protected RPE cells from oxidation and sources of lutein determined the potency of their antioxidant properties and/or biological effects that could be the influences of isolation as well as storing procedures.